Interest Excitation Propagation Model for Information Propagation on micro-blogging - Hongtao Liu; Hongfeng Yun; Hui Chen; Zhaoyu Li; Yu Wu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
An Information propagation model of micro-blogging is proposed for distinguishing normal and non-normal micro-blogging based on users’ interest excitation, which is abbreviated as IEPM(Interest Excitation Propagation Model for Information).The parameters of the model are clearly associated with the actual propagation and can reflect the characteristics of the propagation feature. The model can distinguish users’ non-autonomous behavior in the propagation process of micro-blogging, which can preliminarily judge that it is a non-normal marketing micro-blogging when it doesn’t meet the general propagation in the model. Quantitative analysis and experiment is performed with the dataset from the representative and typical non-normal micro-blogging in Sina micro-blogging, one of the most popular micro-blogging in China. The results show that the model can better reveal the general propagation laws of micro-blogging, and can distinguish normal and non-normal micro-blogging, which will have theoretical and practical significance to a certain degree. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.2734